Renewable Energy Consumption and SDG 7 Progress: The Case of MINT Countries - Supartoyo, Yesi Hendriani (International Journal of Energy Economics and Policy, 2025)
In the context of Mexico, Indonesia, Nigeria, and Turkey (MINT) countries, this study investigates the relationship between renewable energy consumption and access to clean fuels and technologies for cooking as well as access to electricity. When control variables and time-fixed effects were taken into account, panel data regressions were utilized to investigate the effects of specific SDG 7 indicators from the data of Sustainable Development Report for years 2000 – 2021, such as renewable energy consumption, access to clean fuels and technologies for cooking, and access to electricity. For the indicators of access to clean fuels and technologies for cooking, the results of panel data fixed effect regression as a best fit model are shown; these results are statistically significant (p < 0.01).